The Influence of Leadership and Work Discipline on Educational Quality Through Teacher Performance - Prabowo Sasmito; Ernani Hadiyati; Sugeng Mulyono (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2026)
This study examines the influence of leadership and work discipline on education quality through teacher performance. Education quality reflects how well learning processes meet established standards and is influenced by leadership and teacher professionalism. This research used a quantitative approach with an associative design. The population consisted of the principal and civil servant teachers at SDN Sungai Raya in 2022, totaling 40 respondents, using a census method. Data were collected through questionnaires and analyzed using SEM-PLS with Smart PLS software. The results show that leadership and work discipline have a positive and significant effect on teacher performance. However, leadership does not significantly affect education quality, while work discipline and teacher performance do. In addition, leadership has no indirect effect through teacher performance, whereas work discipline shows a significant indirect effect. These findings indicate that work discipline plays a more important role in improving education quality.